DAP gets reality check on extra seats - Abdullah Sani, Asrul Hadi (The Edge Financial Daily, 2012)
PETALING JAYA: Ihe DAP's request for more seats to contest in the next general election has drawn mixed response from its partners in the Pakatan Rakyat (PR) coalition.